Sociodemographic and nutritional situation of children under six years of age in the Nasa Indigenous Reservation, Iquira, Colombia - Juan David Dussán Chaux; Jorge Andrés Ramos-Castañeda; Juan Camilo Calderón-Farfán (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: identify the sociodemographic conditions of the community and determine the prevalence of the nutritional status of children under six years of age in the Nasa Paéz Indigenous Reserve, Rionegro-Huila, Colombia. Methods: cross-sectional descriptive study whose data was obtained from two databases, one of sociodemographic conditions and other anthropometric measurements of children under six years of age. The sample corresponded to the total population of less than six years. The data was analyzed using descriptive statistics using the R Studio 3.4 software. Results: 98.6% of the population is enrolled in the health system. Water consumption comes from 71.6% of non-potable sources. 25.5% of the population has access to wastewater disposal systems. Regarding nutritional status, the prevalence of delay in growth and risk of delay in growth is 43.3% in the population under six months and 69.4% in those aged between six months and six years. Furthermore, 34.3% of children under six months of age are at risk of being overweight. Conclusions: sociodemographic conditions are determined by different inequities, low education levels, inadequate housing, drinking water consumption, as well as a high prevalence of child malnutrition.